Exploring resource use and associated costs in end‐of‐life care for older people with dementia in residential care homes. (6th December 2013) - Amador, Sarah; Goodman, Claire; King, Derek; Ng, Yi Ting; Elmore, Natasha; Mathie, Elspeth; Machen, Ina; Knapp, Martin
<x xml:space="preserve">Abstract</x> Objective The goals of this study are to describe end‐of‐life care costs of older people with dementia (OPWD) residents in care homes (CHs) with no on‐site nursing and evaluate the economic case for an intervention designed to improve end‐of‐life care for OPWD in CHs. Methods Phase 1 tracked for a year, from March 2009, health services received by 133 OPWD in six residential CHs in the East of England. CH and resident characteristics were obtained through standardised assessment tools, interviews with CH managers and publicly available information from the independent regulator of social care services in England. Phase 2 used a modified Appreciative Inquiry intervention that ran for 6 months from January 2011, in three of the six CHs. Wilcoxon matched‐pairs sign‐rank tests were conducted to compare total cost and cost components during Phases 1 and 2 for those residents who had participated in both. Results Costs for each resident in Phase 1 were about £2800 per month, including service, accommodation and medication. Resource use was associated with resident characteristics. The intervention was perceived as having a positive impact on working relationships between CHs and visiting health care practitioners. Following the intervention total service costs fell by 43%. Hospital care costs fell by 88%. Conclusions Results presented here represent early work in an under‐researched area of care. Appreciative Inquiry appears to improve and change working relationships with promising outcomes, but more research is needed to test these findings further with larger samples and more robust controls. Copyright © 2013 John Wiley & Sons, Ltd.